2005
DOI: 10.1021/je0495684
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Equilibria of Water Vapor on Activated Carbon and DAY Zeolite

Abstract: The adsorption equilibria of water vapor on activated carbon and DAY zeolite were measured by a static volumetric method. The equilibrium experiments were conducted at (293, 313, 333, 353, and 373) K and pressures up to 3.4 kPa for activated carbon and 1.9 kPa for DAY zeolite. According to the classification of isotherms, the experimental data are correlated by the Dubinin−Serpinsky and Sips models for activated carbon as well as the Toth, UNILAN, and Sips models for DAY zeolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…42 The adsorption of water on Y-zeolites with Si/Al = 40 from the gas phase was very much lower than that of benzene, 43 and compared to activated carbon the adsorption of water on the DAY zeolite used here was only somewhat greater. 44 In liquid water attractive forces between the condensed water molecules may change the interaction with the pore walls and thus enhance the penetration of the pores. But the extent of pore filling is unknown.…”
Section: Adsorption Of Watermentioning
confidence: 99%
“…42 The adsorption of water on Y-zeolites with Si/Al = 40 from the gas phase was very much lower than that of benzene, 43 and compared to activated carbon the adsorption of water on the DAY zeolite used here was only somewhat greater. 44 In liquid water attractive forces between the condensed water molecules may change the interaction with the pore walls and thus enhance the penetration of the pores. But the extent of pore filling is unknown.…”
Section: Adsorption Of Watermentioning
confidence: 99%
“…The estimation was done on the basis of the literature data published by Ryu et al (2002), Brihi et al (2002) and Kim et al (2005). The residual value analysis shows that Langmuir equation gives an approximation with standard deviation 9.8% for water, 25.9% for toluene and 1.9 % for m-xylene.…”
Section: Mathematical Model Of Fixed Bed Vacuum Desorptionmentioning
confidence: 99%
“…Zeolite DAY 20F was used as adsorbent and model material to be dried. Table 1 shows the properties of zeolite DAY 20F (Kim et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies reported in the literature about the adsorption of water vapor on as synthesized or alkali/alkaline earth metal ion-exchanged synthetic zeolites [16][17][18][19][20][21][22][23][24]: however, very few data related to water vapor adsorption on synthetic zeolites exchanged with strontium is available. Moreover, very less attention has been paid to water vapor adsorption on divalent transition metal ion-exchanged synthetic zeolites [25] and, more generally, on ion-exchanged natural zeolites [26,27].…”
Section: Introductionmentioning
confidence: 99%